The Lagrange Multiplier Test and its Applications to Model Specification in Econometrics - Breusch, T. S.; Pagan, A. R. (Review of Economic Studies, 1980)
T. S. Breusch, A. R. Pagan; The Lagrange Multiplier Test and its Applications to Model Specification in Econometrics, The Review of Economic Studies, Volume 47,